CHARACTER EDUCATION IN ELEMENTARY SCHOOL STUDENTS IN PALEMBANG CITY: A Study of Curriculum Implementation and Character Learning during the Covid-19 Pandemic - Abdurrahmansyah, Abdurrahmansyah; Afriansyah, Syafran; Nasution, Nurseri Hasnah (Conciencia, 2023)
This study aims to explain the pattern of character education during the covid-19 pandemic and see the learn from home policy on weakening the character of elementary school students in Palembang City. The outbreak of the covid-19 pandemic has forced schools to change the tradition and model of implementing education. Basic education institutions must adapt quickly to the covid-19 emergency. The learn from home (LFH) policy has formed a new habit where teachers must use a full online learning system. The implementation of online learning has had an impact on weakening student character. This phenomenological qualitative research succeeded in finding the fact that the character education curriculum development model in elementary schools during the covid-19 pandemic tends to be unclear. The obstacles experienced by teachers in educating character during the Covid-19 pandemic include the absence of school management support in the form of support for learning tools and the weak understanding of teachers and internet-based learning models. The weakening of character in elementary school students is quite serious as a result of the LFH learning system in the form of the emergence of bad attitudes such as annoyance, sadness, anger, low self-esteem, lack of enthusiasm, lack of discipline as a result of the ineffectiveness of the online learning system.